Sorafenib treatment on Chinese patients with advanced hepatocellular carcinoma: A study on prognostic factors of the viral and tumor status - Lee, Shou-Wu (Medicine (Baltimore), 2019)
Sorafenib is of proven efficacy in treating patients of hepatocellular carcinoma (HCC). Our study was aimed to determine the factors influence the sorafenib efficacy. We evaluated data of HCC patients receiving sorafenib from June 2012 to October 2016. All HCC cases were of the Barcelona Clinic Liver Cancer (BCLC) classification stage C. The exclusion criteria: those of BCLC classification stage A or B, with the absence or co-infection of hepatitis B (HBV) and hepatitis C (HCV). The presence of HBV, HCV, macoscopic vascular invasion (MVI) or extrahepatic spread (EHS) was recorded for each patient. Time-to-progression (TTP) and overall survival (OS) were analyzed. Among a total of 90 HCC patients, 48 (53.3%) had HBV infection, 42 (46.7%) had HCV infection, 51 (56.7%) had MVI, and 39 (43.3%) had EHS. Patients with HCV infection showed better TTP and OS than those with HBV infection. Patients with EHS had a longer TTP and OS than those with MVI. For patients with HBV infection, those with EHS had a longer TTP (mean 4.60 vs 2.64 months, P = .002) and OS (mean 6.65 vs 4.53 months, P = .045) compared to those with MVI. Among those with MVI, patients with HBV infection had a poorer TTP (mean 2.64 vs 4.74 months, P = .019) and shorter OS (mean 4.53 vs 7.00 months, P = .059) compared to those with HCV infection. HCC patients with HCV infection or with the presence of EHS showed better sorafenib efficacy.